Pengaruh Pemberian Aktifitas Fisik (Aerobic Exercise) terhadap Tekanan Darah, IMT dan RLPP pada Wanita Obesitas - Yulia Fitri; Nunung Sri Mulyani; Eva Fitrianingsih; Suryana Suryana (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
Based on data from the Indonesian health profile 2011 for the province of Aceh alone prevalence of nutritional status of the adult population (> 18 years) are overweight get into the top ten highest in Indonesia, namely by 10.9% and 13.4% were obese. Granting activity physical (gymnastics healthy heart) is one activity that can affect blood pressure in obese people. Researchers in the United States explains that physical activity at least 15 minutes a day is estimated to decrease by 14% the risk of hypertension obesity which can lead to death. Usefulness study: the development of science can be known benefits of physical activity (aerobic exercise) on blood pressure, BMI and waist-hip ratio in obese women. The study design used was quasi-experimental, with a pre-posttest observational approach, to examine the provision of physical activity (aerobic exercise) on blood pressure, BMI and waist-hip ratio in women Obesity. The results showed that research there is the effect of physical activity (aerobic exercise) for IMT (p = 0,000), and blood pressure (p = 0,000) in obese women but no effect of physical activity on the ratio of the circumference pelvic waist (waist-hip ratio) (p = 0,230). Conclusion: From the results, it can be concluded that there is the influence of physical activity on blood pressure, BMI, and waist-hip ratio, but physical activity does not affect the waist-hip ratio. Keywords: Blood pressure, BMI, waist-hip ratio, obesity